Beyond the Comfort Zone: Strenuous Sports as a Preventive Tactic Against Benign Prostatic Hyperplasia - Wei Zhang; Gang Li; Chengya Hao; Aijun Cheng (American Journal of Men's Health)
Strenuous sports are associated with an enlarged prostate. However, the genetic causality of this association remains unclear. In this study, Mendelian randomization (MR) was used to explore the potential causal relationship between strenuous sports and prostatic hypertrophy. The study utilizes single nucleotide polymorphisms (SNPs) associated with strenuous sports obtained from published genome-wide association studies (GWAS), alongside summarized genetic data related to benign prostatic hyperplasia (BPH) from published GWAS. The primary analytical method used is the Inverse Variance-Weighted (IVW) approach for two-sample MR analysis. Heterogeneity of the results is assessed using Cochran’s Q -statistic, while horizontal pleiotropy is evaluated using MR-Egger. Sensitivity analyses include “leave-one-out” tests. The findings indicate a protective causal effect of strenuous sports on BPH (OR = 0.927, 95% CI: [0.870, 0.988]; p = .020). Results from the Weighted Median (WM) method (OR = 0.904, 95% CI: [0.837, 0.978]; p = .011) support this discovery. Using Mendelian randomization, the study provides reliable causal evidence linking high-intensity exercise to a reduced risk of BPH, overcoming biases seen in traditional observational studies. The study demonstrates a causal protective effect of strenuous sports on BPH, suggesting exercise as a preventive strategy for prostate health.